SARS-CoV-2 pandemic: An emerging public health concern for the poorest in Bangladesh - Rajon Banik; Mahmudur Rahman; Md. Tajuddin Sikder; David Gozal (Elsevier, 2020)
The novel coronavirus (SARS-CoV-2) pandemic is now a global crisis and the poorest in Bangladesh are the most vulnerable. With the whole country being subjected to lockdown measures, millions of poor people are unable to go to work and have lost their incomes, leaving them in profound poverty without access to food and basic health services. Furthermore, living in cramped conditions, lack of health awareness, basic hygiene practices, and failing to maintain social distance measures which are inherently present among the poor, put them at an increased risk of SARS-CoV-2 infection. As the pandemic threatens to expand its devastating grip on Bangladesh, the government and the aid organizations must take urgent and comprehensive initiatives to assist those most in need in this unprecedented health crisis.